Seasonal affective disorder and alcohol abuse disorder in a population-based study. (July 2017) - Morales-Muñoz, Isabel; Koskinen, Seppo; Partonen, Timo
Abstract: Seasonal affective disorder (SAD) is a recurrent major depressive disorder with a seasonal pattern, which is characterized by sad mood, low energy, longer sleep duration and carbohydrate craving. Furthermore, seasonal changes in mood and behavior may be closely related to alcohol use disorder (AUD). Nevertheless, there is scarce research on the study of cognitive impairments in SAD and AUD. We aimed to examine the relationship between the prevalence between SAD and AUD patients, and how cognitive functioning might be related to these variables. To do this, a sample of 8135 Finnish subjects was invited to take part in the population-based Health 2011 Survey, of whom 5903 did participate and 4554 were interviewed for mental health status with the Munich version of Composite International Diagnostic Interview. They also completed the modified Seasonal Pattern Assessment Questionnaire, the Mini–Mental State Examination, the category (animals) verbal fluency test, and the Rey Auditory Verbal Learning Test. Our results reveal the existence of a strong link between SAD and AUD in a large sample of Finnish population, as well as association between SAD and short-term memory problems. Highlights: We used a large sample of 4880 Finnish participants. Participants with seasonal affective disorder showed higher prevalence of alcohol disorders. Seasonal affective disorder was related to short-term memory problems. Cognitive functioning was not affected in our Finnish population with alcohol use disorder.